Characterization of IEEE802.11 WLAN Implementing on Excavator: Can We Use IEEE802.11 for i-construction? - Hamamoto, Ryo; Endo, Kazuomi; Nakagawa, Tomohiro; Togo, Hiroshi; Tanaka, Junya; Kanazawa, Kouji; Ishihara, Kentaro; Kawagoe, Yuchi; Aso, Takahito (EAI Endorsed Transactions on Internet of Things, 2022)
As network systems become more sophisticated, through network systems, the automatic/remote-automatic/remote-control technology is spreading to construction machinery. These technologies are supported by wireless communication. Currently, IEEE802.11 is a widely used wireless communication standard. This IEEE802.11 standard is expected to improve the usability of construction machinery, similar to other mobilities, such as vehicles. However, its communication characteristics are unknown. Here, we evaluate the performance of a wireless local area network (WLAN) comprising wireless communication modules implemented in an excavator. In particular, we focus on the throughput when sender and receiver positions are changed. Experimental results were used to characterise the WLAN device communication between a PC and a communication controller. We found that the IEEE802.11 WLAN has been confirmed as having applicability to i-construction.